2017
DOI: 10.1371/journal.pone.0177559
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of Merozoite Surface Protein-2 (MSP-2) in Plasmodium falciparum isolates from Pawe District, North West Ethiopia

Abstract: BackgroundIn malaria endemic regions, Plasmodium falciparum infection is characterized by extensive genetic diversity. Describing this diversity provides important information about the local malaria situation. This study was conducted to evaluate the extent of genetic diversity of P. falciparum in Pawe district, North West Ethiopia, using the highly polymorphic merozoite surface protein 2 gene.MethodsAtotal of 92 isolates from patients with uncomplicated P. falciparum attending Pawe Health Centre were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
8
21
7
Order By: Relevance
“…The present study found that nearly three-quarters of the isolates harboured multiple genotypes, with about one-quarter monoclonal. This is a similar finding to a previous study from Northwest Ethiopia that only analysed msp - 2 [ 16 ]. However, it is a significantly higher proportion with multiple clones than many of the locations sampled by the International Centers of Excellence for Malaria Research [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found that nearly three-quarters of the isolates harboured multiple genotypes, with about one-quarter monoclonal. This is a similar finding to a previous study from Northwest Ethiopia that only analysed msp - 2 [ 16 ]. However, it is a significantly higher proportion with multiple clones than many of the locations sampled by the International Centers of Excellence for Malaria Research [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…To date, there has been limited assessment of genetic diversity of P. falciparum in Ethiopia [ 15 , 16 ], despite scaling up of national malaria control interventions [ 17 ]. This study aimed to characterize the genetic diversity and allele frequencies of msp - 1, msp - 2 and glurp genes of P. falciparum isolates from uncomplicated malaria patients in Humera along the Ethiopian border.…”
Section: Introductionmentioning
confidence: 99%
“…3 ), most likely because the frequency of infectious mosquito bites in high transmission settings, that could result in additional inoculum of variant parasites is higher than in lower transmission settings [ 49 ]. This finding supports general notion that Low transmission settings are commonly associated with reduced MOI in malaria endemic countries [ 50 , 51 ]. The geometric mean MOI differed significantly across the time points in Abura (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 80% of the isolates harboured more than one parasite genotype identi ed by the presence of two or more alleles of one or both genes with the overall mean MOI being 3.2 (95% CI: 2.87-3.46). The overall MOI value reported in this study was higher than previously reported studies, including Ethiopia (MOI: 1.8 -2.6) between 2015-2018 [42,43,44], Brazzaville, Republic of Congo (MOI: 2.2) [16] in 2011 and Bobo-Dioulasso, Burkina Faso (MOI: 1.95) [62]. In contrast to study reported in Bioko Island, Equatorial Guinea (MOI: 5.51) [53] in 2018 and Gabon (MOI: 4.0) [63] in 2018.…”
Section: Discussioncontrasting
confidence: 83%